Effects of the COVID‐19 pandemic on clinically diagnosed psychiatric disorders in persons with type 2 diabetes. Issue 8 (20th April 2022) - Kowall, Bernd; Kostev, Karel; Landgraf, Rüdiger; Hauner, Hans; Bierwirth, Ralf; Rathmann, Wolfgang
Abstract: Aims: To examine whether the incidence rates of diagnosed depression, anxiety disorders and stress reactions, as well as prescription rates of antidepressants and anxiolytics were higher during the COVID‐19 pandemic than before in persons with type 2 diabetes in Germany. Contrary to earlier studies, clinical diagnoses of psychiatric disorders (ICD classification) were used. Methods: The German Disease Analyzer (DA) database is an outpatient database containing routine data on patients´ diseases and treatments provided by a representative panel of physician practices selected from across Germany. We assessed incidence rates of depressive disorders (ICD‐10: F32, F33), anxiety disorders (F41) and stress reactions (F43) in quarters from January 2019 to March 2021 in 95, 765 people with type 2 diabetes included in the DA in 2019 (mean age 68.9 years, 58% men). Prescription rates of antidepressants and anxiolytics in quarters from January 2020 to March 2021 were compared with prescription rates from 1 year earlier. Results: During the study period, the incidence rate of newly diagnosed depressive disorders in persons with type 2 diabetes declined slightly, while the incidence rates of anxiety and stress disorders remained largely constant. The rates of new prescriptions for antidepressants and anxiolytics were lower in all quarters of 2020 and in the first quarter of 2021 than in the quarters 1 year earlier. Diabetes‐related complications were more prevalent in persons with incident psychiatric disorders than in those without. Conclusions: No increase in the incidence rates of clinically diagnosed psychiatric disorders was observed during the COVID‐19 pandemic in Germany in persons with type 2 diabetes.